PENGARUH MODEL PJBL BERBASIS KEGIATAN PASAR SETEMPAT TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V PADA MATA PELAJARAN IPAS DI UPT SPF SD INPRES HARTACO INDAH - Syahrani, Ashara Isma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: (1) the description of the implementation of the PjBL model based on local market activities, (2) the description of students’ critical thinking skills in IPAS, and (3) the effect of the Project Based Learning (PjBL) model based on local market activities on students’ critical thinking skills. The approach used in this study was quantitative, employing a quasi-experimental method with a nonequivalent control group design. The study involved two groups, namely an experimental class consisting of 30 students and a control class consisting of 30 students. Data collection techniques included observation, tests (pretest and posttest), and documentation. The results of the study indicate that: (1) the implementation of the PjBL model based on local market activities, as reflected in observation sheets at each meeting, showed that the learning process was carried out very well through teacher activities with an average score of 92% (Very Good category) and student activities with an average score of 84% (Good category); (2) the description of students’ critical thinking skills in IPAS showed that the average pretest score of the experimental class was 52.57 and increased to 83.73 in the posttest; and (3) based on the results of inferential analysis using the Independent Sample t-Test, the significance value obtained was p=0.000 (p<0.05). It can be concluded that the implementation of the PjBL model based on local market activities has a significant effect on the critical thinking skills of fifth-grade students in IPAS at UPT SPF SD Inpres Hartaco Indah.